2012
DOI: 10.1155/2012/457031
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flaxseed Oil Protects against Bleomycin-Induced Pulmonary Fibrosis in Rats

Abstract: Bleomycin, a widely used antineoplastic agent, has been associated with severe pulmonary toxicity, primarily fibrosis. Previous work has shown a reduction in bleomycin-induced lung pathology by long-chain omega-3 fatty acids. Treatment by short-chain omega-3 fatty acids, α-linolenic acid, found in dietary flaxseed oil may also reduce lung fibrosis, as previously evidenced in the kidney. To test this hypothesis, 72 rats were divided between diets receiving either 15% (w/w) flaxseed oil or 15% (w/w) corn oil (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…FO enriched in PUFA (ALA) and phytoestrogenic lignans provide one such dietary source of biologically active components that has been shown to be co-preventive 20 and co-therapeutic 10 in a wide variety of ailments. The two main fatty acids, linoleic and alpha linolenic acid, are like vitamins: we cannot make them.…”
Section: Discussionmentioning
confidence: 99%
“…FO enriched in PUFA (ALA) and phytoestrogenic lignans provide one such dietary source of biologically active components that has been shown to be co-preventive 20 and co-therapeutic 10 in a wide variety of ailments. The two main fatty acids, linoleic and alpha linolenic acid, are like vitamins: we cannot make them.…”
Section: Discussionmentioning
confidence: 99%
“…Other researcher reported that bleomycin increases lung epithelial cell apoptosis in a reactive oxygen species (ROS)-dependent manner [28]. BLM-induced pulmonary fibrosis was explained by some authors who reported that the chemotherapeutic mechanism of BLM results from the chelation of iron ions with oxygen, which leads to production of DNA-cleaving superoxide, and also hydroxide free radicals [29]. It is the increased production of ROS that lead to bleomycin's pulmonary toxicity, and may eventually lead to lung fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of the diet with flaxseeds triggers anti-fibrotic effects, both before and after lung damage [ 128 , 129 ], doubling the survival rate when analysed as a therapeutic agent. When flaxseeds are given as oil, this treatment also reduces lung damage, as previously mentioned, an effect that is attributed to their high short-chain ω-3 PUFA content [ 51 , 52 ]. However, it has been demonstrated that lignans from wholegrain flaxseed decrease inflammation, lung injury and eventual fibrosis while it improves survival after radiation exposure, evidencing that it is a bioactive component responsible for lung damage mitigation [ 130 ].…”
Section: The Role Of Nutritional Factors In Ipfmentioning
confidence: 98%
“…In the context of lung fibrosis, a relevant example of the importance of dietary lipids in the perinatal period for the development of diseases in adulthood comes from an experiment in which maternal diet supplementation with docosahexaenoic acid attenuated pulmonary fibrosis and improved lung function in mouse pups exposed to perinatal inflammation [ 49 ]. Furthermore, the mitigation of lung fibrosis has been demonstrated with long-chain ω-3 PUFAs (docosahexaenoic acid (22:6, ω-3)) [ 50 ], short-chain ω-3 PUFA present in flaxseed oil [ 51 , 52 ], and with ω-6 PUFAs, such as γ-linolenic acid (18:3, ω-6) [ 53 ]. The effects attributed to the anti-fibrotic properties of PUFA could be mediated, in part, through their conversion to resolvinD 1 , which inhibits EMT in human alveolar type II cells [ 54 ], and through peroxisome proliferator-activated receptor γ (PPARγ).…”
Section: The Role Of Nutritional Factors In Ipfmentioning
confidence: 99%